Synthesis of 1,2,4-Triazolo[5,1-b][1,3]-thiazin-7-ones Catalyzed by Pentafluorophenylammonium Triflate - Montazeri, N.; Pourshamsian, K.; Divsalar, A.; Ghoorchi-Beigi, M. (Asian Journal of Chemistry, 2012)
Pentafluorophenylammonium triflate has been found to be an outstanding catalyst for the cyclization of 3-(4H-1,2,4-triazol-3-ylsulfanyl)-acrylic acids into 1,2,4-triazolo[5,1- b][1,3]thiazin-7-ones under solvent-free microwave irradiation and conventional heating. Taking into account environmental and economical considerations, the protocol presented here has the merits of environmentally benign, simple operation, convenient work-up and good yields. Furthermore, the catalyst can be easily recovered and reused without losing its activity.